The Princess And The Pea - De La Touche, Grace (Grandreams Ltd, 1993)
A long time ago, there lived a prince who was looking for someone very special to marry.Although the handsome prince meets ladies blessed with beauty, wealth, and brains, he knows in his heart that none is the true princess he longs for. Then, one stormy night, a wet, disheveled, and very weary young woman knocks at the castle door. Could she be his queen? One tiny pea buried underneath twenty soft mattresses might reveal the truth$1! =s
Keywords: Fairy Tales & Folklore; General; Juvenile Fiction